HAFNIUM ISOTOPIC COMPOSITION IN ZIRCONS FROM ANORTHOSITE-RAPAKIVI GRANITE MASSIFS OF THE UKRAINIAN SHIELD - SHUMLIANSKYI, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Paper deals with results of investigation hafnium isotopic composition in zircons separated from rocks of the Korosten and KorsunNovomirgorod plutons. Initial melts of the Korosten pluton originated mainly from the depleted mantle; however, portion of the depleted mantle in the source region decreased with time in benefit of low-crustal material. In contrast, source of initial melts of the KorsunNovomirgorod pluton did not contain any sufficient portion of the depleted mantle material. The source was represented by relatively old crustal rocks.